2010
DOI: 10.1021/jf102552b
|View full text |Cite
|
Sign up to set email alerts
|

High Molecular Weight Persimmon (Diospyros kaki L.) Proanthocyanidin: A Highly Galloylated, A-Linked Tannin with an Unusual Flavonol Terminal Unit, Myricetin

Abstract: MALDI-TOF MS suggested that the high molecular weight proanthocyanidin (condensed tannin) from persimmon (Diospyros kaki L.) pulp comprised a heteropolyflavanol series with flavan-3-O-galloylated extenders, flavan-3-ol and flavonol terminal units, and A-type interflavan linkages. Thiolysis-HPLC-ESI-MS with DAD, electrochemical, and ESI-MS detection confirmed a previously unreported terminal unit, the flavonol myricetin, in addition to the typical flavan-3-ols catechin and epigallocatechin gallate. The extender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 40 publications
7
126
0
1
Order By: Relevance
“…Peak 3 was identified as (epi)gallocatechin benzylthioether (MW = 428) and peak 4 was identified as (epi)gallocatechin-3-O-gallate benzylthioether (MW = 580). Similar mass spectra data for these compounds were reported in proanthocyanidins from persimmon fruit (Li et al, 2010). The compound eluting in peak 5 was identified as (epi)catechin benzylthioether (MW = 412).…”
supporting
confidence: 57%
“…Peak 3 was identified as (epi)gallocatechin benzylthioether (MW = 428) and peak 4 was identified as (epi)gallocatechin-3-O-gallate benzylthioether (MW = 580). Similar mass spectra data for these compounds were reported in proanthocyanidins from persimmon fruit (Li et al, 2010). The compound eluting in peak 5 was identified as (epi)catechin benzylthioether (MW = 412).…”
supporting
confidence: 57%
“…First, polyphenols may interact with chromatographic stationary phases, such as PL-gel, leading to overestimates in molecular weight (Williams et al 1983). Second, calibration plots generated using commercially available standards such as polystyrene tend to underestimate CT sizes (Li et al 2010). Finally, the relationship between hydrodynamic volume and molecular weight appears to be a complex function of the subunit composition for different polyphenols, so even with CT standards it is difficult to generate a reliable calibration plot (Kennedy & Taylor 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent weight-average molecular weights of CT purified from these legumes, relative to polystyrene standards, ranged from 552 to 1483 Da (Table 1). The two most widely used methods for establishing the molecular weight of CT are thiolysis followed by quantitative HPLC analysis of the extender and terminal units (Li et al 2010) or GPC (Bae et al 1994). Thiolysis provides accurate estimates of the mean degree of polymerization, but not the molecular weight distribution (Kennedy & Taylor 2003).…”
Section: Resultsmentioning
confidence: 99%
“…For polymeric proanthocyanidins, antioxidant activities are probably a consequence of structural features such as the monomeric flavan-3-ol units, the types of interflavan bonds, and the degree of polymerization. Our previous work (Li, Leverence, et al, 2010) showed that HMWPT has a unique structure compared to other plant proanthocyanidins: It comprises an …”
Section: Antioxidant Effect Of Hmwpt On Bromobenzene Induced Oxidativmentioning
confidence: 99%
“…The HMWPT was characterized by MALDI-TOF, thiolysis-HPLC-ESI-MS and NMR (Li, Leverence, et al, 2010). The mean degree of polymerization of HMWPT was estimated to be 26 by thiolysis.…”
Section: Plant Materials and Sample Preparationmentioning
confidence: 99%